THE MEDIATING ROLE OF PSYCHOLOGICAL EMPOWERMENT IN THE RELATIONSHIP BETWEEN HIGH-PERFORMANCE WORK SYSTEMS AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Arefin, Shamsul; Arif, Ishtiaque; Raquib, Muhammad (European Scientific Journal, ESJ, 2015)
This study develops a mediation model in which high-performance work systems (HPWS) affect organizational citizenship behavior through psychological empowerment. Using a sample of 247 employees employed by three large manufacturing firms in Bangladesh, results from structural equation modeling and hierarchical regression analyses showed that psychological empowerment mediated the relationship between HPWS and organizational citizenship behavior. The theoretical and practical implications of these findings are discussed.